Image Processing For Improving Image Quality Using The Improvement Method Of Image And Improvement Image - Fitri Rizani (Universitas Mulia, 2019)
Better computer skills in various fields, better in the field of image processing through a process of increasing image quality that is once received. Help empower the computer at any time needs to be improved. Image Quality Improvement can be made with various techniques; one of them is by Improving Image Quality with Image Brightness and Image Sharpening methods. The process begins with capturing images followed using increasing competence, image contrast, and sharpening. The results of image processing are generated by changes in the resulting image and changes in image histograms.